2011
DOI: 10.1111/j.1365-2559.2011.03958.x
|View full text |Cite
|
Sign up to set email alerts
|

Spherule-like acellular stroma in clear cell carcinoma of the ovary: its utility in frozen section diagnosis

Abstract: and to investigate its activity in combination with cytotoxic drugs. 5 We demonstrated that the selected case of c-KIT overexpression in squamous cell carcinoma of the uterine cervix from our previous preliminary report also showed significant PDGFRA protein overexpression, but no PDGFRA gene activating mutations. Although the tissue materials used in both the aforementioned studies (Taja-Chayeb 6 and Longatto-Filho 7 ) were not restricted to the squamous cell type, our findings are in agreement with the descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It is known that hyaluronan is synthesized at the cell membranes and secreted into the intercellular spaces, as well as into the free spaces [10]. Our previous study showed that spherule-like mucoid stroma is a consequence of accumulation of hyaluronan in the intercellular spaces [5]. This was also supported by the present study: JHOC-5, which had less potential for hyaluronan synthesis than HAC-2, rarely showed spherulelike mucoid stroma but just showed distribution of hyaluronan at the cell membranes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is known that hyaluronan is synthesized at the cell membranes and secreted into the intercellular spaces, as well as into the free spaces [10]. Our previous study showed that spherule-like mucoid stroma is a consequence of accumulation of hyaluronan in the intercellular spaces [5]. This was also supported by the present study: JHOC-5, which had less potential for hyaluronan synthesis than HAC-2, rarely showed spherulelike mucoid stroma but just showed distribution of hyaluronan at the cell membranes.…”
Section: Discussionmentioning
confidence: 98%
“…The main constituents of the amorphous material are basement membrane materials, including laminin and type IV collagen [3]. Immunohistochemical and ultrastructural studies showed that tumor cells themselves can produce basement membrane materials and subsequently form basement membrane-like structures [3][4][5]. However, it remains unclear whether tumor cells can form hyalinized stroma by themselves or if cooperation with stromal cells is required.…”
Section: Introductionmentioning
confidence: 99%
“…They commonly occupy the cores of small papillae, and they are often admixed: both stromas represent different phases of the stromal remodeling process, and are considered complementary diagnostic signatures of CCCs. 8,10 Hyalinized stroma is composed of basement membrane materials, including laminin-5 and type IV collagen, 6,11 whereas mucoid stroma is rich in glycosaminoglycan including hyaluronan ( Fig. 3a).…”
Section: Cancer Stromamentioning
confidence: 99%
“…8 Despite the presence of abundant ECM, both stromas are rarely associated with fibroblasts, which are the major sources of ECM. By using CCC cell lines, the author and colleagues showed that CCC cells produce ECM, 8,10,12,13 and that hyalinized/mucoid stroma is a consequence of the accumulation of CCC-derived ECM in intercellular spaces. 10,12 Clear cell carcinoma is often associated with clear cell borderline adenofibroma.…”
Section: Cancer Stromamentioning
confidence: 99%